IMPLEMENTASI MANAJEMEN MUTU TERPADU BIDANG TENAGA PENDIDIK DI MADRASAH - Bani, Bani (e-Journal STAI Muhammadiyah Tulungagung, 2015)
Madrasah constitutes first unit and foremost in perform functioning education forms and increase man resource. The program and that education development project expected gets to prop education upgrade effort at madrasah, one of it by applying management in educational whole ala and gets orientation on quality. One of educational management that gets orientation on that quality is coherent Quality Management (MMT). Coherent Quality management constitute orderly effort and most coordination for continually fix service quality, so its focus is led to customer, in this case educative participant, participant oldster is taught, graduated user, teacher, employee, government and society.â